Notes on the Isard and Chenery-Moses Interregional Input-Output Models - John M. Hartwick (Queen's University, Department of Economics, 1970)
Interregional input-output models have seldom been empirically articulated owing no doubt to the inordinate demands made on research teams to collect data on economic flows and to prepare the oeffecients required int he models. This paper talks about a more recent model, which is that of Leontief and Strout, which makes use of the gravity theory for estimating interregional flows.
Keywords: 330